LC-MS/MS Method for Determination of Megestrol in Human Plasma and Its Application in Bioequivalence Study - 李帆 邹小娟 郑恒 向一 (Journal of Huazhong University of Science and Technology. Medical sciences, 2013)
A rapid and highly selective liquid chromatography-tandem mass spectrometric （LC-MS/MS） method for the determination of megestrol in human plasma was described using medry- sone as internal standard （IS）. Blood samples were collected from 20 healthy volunteers after oral ad- ministration of 160 mg megestrol acetate dispersible tablets. The analytes were extracted by liq- uid-liquid extraction procedure and separated on a hanbon lichrospher column with the mobile phase of methanol and water containing 0.1% formic acid and 20 mmol/L ammonium acetate （5：1, v/v）. Positive ion electrospray ionization with multiple reaction-monitoring mode （MRM） was employed by monitor- ing the transitions m/z 385.5-325.4 and m/z 387.5-327.4 for megestrol and medrysone, respectively. Under the isocratic separation conditions, the chromatographic rim time was approximately 2.54 min for megestrol and 2.59 min for medrysone. The calibration curve range was from 0.5 to 200.0 ng/mL. The inter-batch and intra-batch precision and accuracy were less than 5.2% relative standard deviation （RSD） and 6.4% relative error （RE）. The proposed method was successfully applied in the bioequivalence study of megestrol acetate dispersible tablets.